Topiramate add-on treatment associated with normalization of prolactin levels in a patient with schizophrenia - Huang Y (Dove Medical Press, 2017)
Yinglin Huang,1,2 Huan Ma,1 Yuan Wang,2 Miao Peng,2 Gang Zhu1 1Department of Psychiatry, The First Affiliated Hospital of China Medical University, 2Department of Psychiatry, Shengjing Hospital of China Medical University, Shenyang, China Abstract: Topiramate has been used increasingly in the management of psychiatric conditions. Clinical trials demonstrated that topiramate augmentation was effective in controlling negative symptoms in schizophrenia. This case report presents a case of a 38-year-old man with schizophrenia who achieved full negative symptom remission upon the adjunctive use of topiramate. However, the remarkable finding of this case is the concomitant decrease in the level of prolactin when topiramate (50 mg/day) was started and the rebound after discontinuation of topiramate. Previous studies stated that topiramate could prevent antipsychotic-induced weight gain and adverse metabolic effects. To the authors’ knowledge, no study has reported that topiramate augmentation could be a treatment strategy for antipsychotic-induced hyperprolactinemia. This finding could be verified by well-designed clinical trials. Keywords: topiramate, prolactin, schizophrenia, antipsychotics, dopamine, alpha-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA)